Pharmacokinetics of Adjusted-Dose Lopinavir-Ritonavir Combined with Rifampin in Healthy Volunteers - la Porte, C. J. L. (American Society for Microbiology, 2004)
Coadministration of lopinavir-ritonavir, an antiretroviral protease inhibitor, at the standard dose (400/100 mg twice a day [BID]) with the antituberculous agent rifampin is contraindicated because of a significant pharmacokinetic interaction due to induction of cytochrome P450 3A by rifampin. In the present study, two adjusted-dose regimens of lopinavir-ritonavir were tested in combination with rifampin. Thirty-two healthy subjects participated in a randomized, two-arm, open-label, multiple-dose, within-subject controlled study. All subjects were treated with lopinavir-ritonavir at 400/100 mg BID from days 1 to 15. From days 16 to 24, the subjects in arm 1 received lopinavir-ritonavir at 800/200 mg BID in a dose titration, and the subjects in arm 2 received lopinavir-ritonavir at 400/400 mg BID in a dose titration. Rifampin was given at 600 mg once daily to all subjects from days 11 to 24. The multiple-dose pharmacokinetics of lopinavir, ritonavir, and rifampin were assessed. Twelve of 32 subjects withdrew from the study. For nine subjects lopinavir-ritonavir combined with rifampin resulted in liver enzyme level elevations. Pharmacokinetic data for 19 subjects were evaluable. Geometric mean ratios for the lopinavir minimum concentration in serum and the maximum concentration in serum (C(max)) on day 24 versus that on day 10 were 0.43 (90% confidence interval [CI], 0.19 to 0.96) and 1.02 (90% CI, 0.85 to 1.23), respectively, for arm 1 (n = 10) and 1.03 (90% CI, 0.68 to 1.56) and 0.93 (90% CI, 0.81 to 1.07), respectively, for arm 2 (n = 9). Ritonavir exposure increased from days 10 to 24 in both arms. The geometric mean C(max) of rifampin was 13.5 mg/liter (day 24) and was similar between the two arms. Adjusted-dose regimens of lopinavir-ritonavir in combination with therapeutic drug monitoring and monitoring of liver function may allow concomitant use of rifampin.